2017
DOI: 10.1038/s41467-017-00196-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of breast cancer CTCs associated with brain metastasis

Abstract: The enumeration of EpCAM-positive circulating tumor cells (CTCs) has allowed estimation of overall metastatic burden in breast cancer patients. However, a thorough understanding of CTCs associated with breast cancer brain metastasis (BCBM) is necessary for early identification and evaluation of treatment response to BCBM. Here we report that BCBM CTCs is enriched in a distinct sub-population of cells identifiable by their biomarker expression and mutational content. Deriving from a comprehensive analysis of CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(214 citation statements)
references
References 64 publications
4
206
0
Order By: Relevance
“…EpCAM-negative breast cancer CTCs containing stem-cell properties (CD44 +/CD24−) have been isolated by multiparametric flow cytometry from blood of breast cancer patients. These cells possessed high competence to generate breast cancer brain metastasis in xenografts [138,139]. Incidentally, breast cancer is the second most common cancer to metastasize to the brain and the prognosis of patient diagnosed with brain metastasis remains poor [140].…”
Section: Methods To Isolate and Identify Ctcmentioning
confidence: 99%
“…EpCAM-negative breast cancer CTCs containing stem-cell properties (CD44 +/CD24−) have been isolated by multiparametric flow cytometry from blood of breast cancer patients. These cells possessed high competence to generate breast cancer brain metastasis in xenografts [138,139]. Incidentally, breast cancer is the second most common cancer to metastasize to the brain and the prognosis of patient diagnosed with brain metastasis remains poor [140].…”
Section: Methods To Isolate and Identify Ctcmentioning
confidence: 99%
“…Both in vitro and in vivo BC studies have been performed using GIP which demonstrated both anti-growth and anti-metastatic activities. For example, in a microarray study, GIP was found to down-regulate the mRNA (1.5 to 8 fold) of many proteins detected in the "CTC signature" of the BC-derived circulating cells described by Boral et al [10] . Such proteins included CD44, CD40, TNF, NFkB, IL-1 receptor, Serpin I-1, and p53 AIP1 among others.…”
Section: Afp-derived Peptides Ctcs and Metastasismentioning
confidence: 99%
“…In a recent study using breast cancer (BC) cells, Boral et al [10] reasoned that mRNA characterization of CTCs from BC derived cells could provide a means for early diagnosis of brain metastases; this knowledge could aid in planning therapeutic strategies and determining the effectiveness of targeting metastatic cells. Boral's studies confirmed that patients with BC produce CTCs that express high levels of biomarkers that are associated with regulation of cell growth, proliferation, and signal transduction pathways directly involved with metastasis.…”
Section: Background Studiesmentioning
confidence: 99%
See 2 more Smart Citations